The graduate advisor handbook a student-centered approach - Shore, Bruce M. (Chicago guides to academic life, 2014)
In the sink-or-swim world of academia, a great graduate advisor can be a lifesaver. But with university budgets shrinking and free time evaporating, advisors often need a mentor themselves to learn how to best support their advisees. This book demystifies the advisor-student relationship, and provides tips and advice to students and advisors.